Understanding Mathematics Inquiry-Based Classroom Practice: Teacher’s Actions And Intentions - Canavarro, Ana Paula (2014)
This paper focuses on the inquiry-based teaching of mathematics (Stein, Engle, Smith & Hughes, 2008). It is our purpose to deepen our understanding of this complex practice of the teachers, considering both the actions and the intentions behind the actions they perform (Ponte & Chapman, 2006). We analyse the case of one of the teachers we work with in a broader Design Research project where the research on classroom practice and the planning of teacher training develop in articulation (Canavarro, Oliveira, & Menezes, 2012). We provide a description of the actions the teacher performed when students work autonomously on a mathematical task, as well as her reasons to justify her actions. We conclude that the practice of the teacher is oriented by to different but interrelated main purposes: